Relational Memory at Short and Long Delays in Individuals With Moderate-Severe Traumatic Brain Injury - Morrow, Emily L.; Dulas, Michael R.; Cohen, Neal J.; Duff, Melissa C. (Frontiers in Human Neuroscience, 2020)
Memory deficits are a common and frequently-cited consequence of moderate-severe traumatic brain injury (TBI). However, we know less about how TBI affects relational memory, which allows the binding of the arbitrary elements of an experience and the flexible use and recombination of relational representations in novel situations. Relational memory is of special interest for individuals with TBI, given the vulnerability of the hippocampus to injury mechanisms, as well as a growing body of literature establishing the role of relational memory in flexible and goal-directed behavior. In this study, participants with and without a history of moderate-severe TBI completed a continuous relational memory task for face-scene pairings. Participants with TBI exhibited a disruption in relational memory not only when tested after a delay, but also when tested with no experimenterimposed delay after stimulus presentation. Further, canonical assessments of working and episodic memory did not correspond with performance on the face-scene task, providing evidence that this task may tap into relational memory differently and with greater sensitivity than in standardized assessments of TBI. These results highlight the need for rigorous assessment of relational memory in TBI, which is likely to detect deficits that have specific consequences for community reintegration and long-term functional outcomes.